Soil Wind Erodibility Based on Dry Aggregate‐Size Distribution in the Tarim Basin. Issue 6 (17th October 2014) - Li, Xinhu; Feng, Guanglong; Sharratt, Brenton S.; Zheng, Zehao; Pi, Huawei; Gao, Fei
Abstract : The Tarim Basin is an important source of airborne particulate matter that contributes to poor air quality in China. However, little attention has been given to estimating wind erodibility of soils in the region. The objective of this study was to determine the soil wind erodibility for four land use types in the Tarim Basin. Wind erodibility was determined from the dry aggregate size distribution of soils collected from desert, farmland, forest, and shrubland environments in spring 2013. Our analysis revealed that the percentage of soil mass composed of aggregates <840 μm in diameter (erodible fraction) ranged from 5.2 to 99.9% across sites with a mean of 58.9% across land use types. The four land use types had a high content of erodible aggregates. The mean percentage of soil mass which was comprised of saltation‐size (500–100 μm in diameter) and suspension‐size material (<100 μm in diameter) was 15.0 and 39.0%, respectively, across land use types. The desert had the highest potential for saltation activity and suspension. Our results suggest that all land use types examined in this study have potential to contribute to the atmospheric dust load in the Tarim Basin and to transcontinental and transoceanic transport of dust.